2016
DOI: 10.1038/ncomms10151
|View full text |Cite
|
Sign up to set email alerts
|

Cep57 is a Mis12-interacting kinetochore protein involved in kinetochore targeting of Mad1–Mad2

Abstract: The spindle assembly checkpoint (SAC) arrests cells in mitosis by sensing unattached kinetochores, until all chromosomes are bi-oriented by spindle microtubules. Kinetochore accumulation of the SAC component Mad1–Mad2 is crucial for SAC activation. However, the mechanism by which Mad1–Mad2 accumulation at kinetochores is regulated is not clear. Here we find that Cep57 is localized to kinetochores in human cells, and binds to Mis12, a KMN (KNL1/Mis12 complex/Ndc80 complex) network component. Cep57 also interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 66 publications
0
41
1
Order By: Relevance
“…1F and 2A), which suggests that TbCEP57 may function as a basal body connector. Unlike TbCEP57, however, the CEP57 homologs in Xenopus laevis and humans localize to centrosomes and kinetochores and are required for spindle assembly and kinetochore-microtubule attachment (23, 24). Moreover, the human CEP57 homolog also functions as a NEDD1-binding pericentriolar material component to maintain spindle pole integrity (25).…”
Section: Discussionmentioning
confidence: 99%
“…1F and 2A), which suggests that TbCEP57 may function as a basal body connector. Unlike TbCEP57, however, the CEP57 homologs in Xenopus laevis and humans localize to centrosomes and kinetochores and are required for spindle assembly and kinetochore-microtubule attachment (23, 24). Moreover, the human CEP57 homolog also functions as a NEDD1-binding pericentriolar material component to maintain spindle pole integrity (25).…”
Section: Discussionmentioning
confidence: 99%
“…CEP57 was shown to localize to kinetochore via its interaction with the kinetochore-microtubule protein MIS12 and activates the SAC by recruitment of MAD1-MAD2 components of MCC to the kinetochore. CEP57-depleted cells demonstrated attenuated SAC signaling, resulting in premature entry into anaphase that led to an increased rate of chromosome lagging (Zhou et al 2016). The authors also showed that CEP57 facilitates SAC silencing through competition of microtubule-binding activity with MAD1 (Zhou et al 2016), suggesting that constitutional aneuploidy associated with CEP57 loss is potentially contributed by increased chromosomal mis-segregation due to impaired CEP57 regulation of kinetochore-microtubule attachments via MAD1-MAD2.…”
Section: Germline Mutations Affecting Kinetochore-microtubule Dynamicsmentioning
confidence: 94%
“…CEP57-depleted cells demonstrated attenuated SAC signaling, resulting in premature entry into anaphase that led to an increased rate of chromosome lagging (Zhou et al 2016). The authors also showed that CEP57 facilitates SAC silencing through competition of microtubule-binding activity with MAD1 (Zhou et al 2016), suggesting that constitutional aneuploidy associated with CEP57 loss is potentially contributed by increased chromosomal mis-segregation due to impaired CEP57 regulation of kinetochore-microtubule attachments via MAD1-MAD2. Interestingly, loss of function of SNF5, a core component of the SWI/SNF chromatin remodeling complex, has been found to impair SAC signaling and promote chromosome mis-segregation in part by causing overexpression of MAD2 (Vries et al 2005).…”
Section: Germline Mutations Affecting Kinetochore-microtubule Dynamicsmentioning
confidence: 94%
See 1 more Smart Citation
“…Cep57, a FGF-2 binding and trafficking protein, has been reported to be required for normal centriole duplication, proper chromosome segregation, PCM organization and centriole engagement (Bossard et al, 2003; Cuevas et al, 2013; Meunier et al, 2009; Snape et al, 2011; Wu et al, 2012; Zhou et al, 2016). Cep57, Cep63 and Cep152 form a stable complex at the proximal end of the centrioles and Cep57 is the proximity interactor of Cep63 (Firat-Karalar et al, 2014; Fortun et al, 2018; Lukinavicius et al, 2013; Sieben et al, 2018), suggesting that Cep57 may act as the upstream protein to target the Cep63-Cep152 complex for centriole duplication.…”
Section: Introductionmentioning
confidence: 99%